2015
DOI: 10.1134/s0026893315020107
|View full text |Cite
|
Sign up to set email alerts
|

Methods to study the RNA-protein interactions

Abstract: RNA binding proteins (RBPs) play an important role in regulating gene expression at the post transcriptional level, including the steps of pre mRNA splicing, polyadenylation, mRNA stabilization, mRNA export from the nucleus to the cytoplasm, mRNA localization, and translation. RBPs regulate these processes primarily by binding to specific sequence elements in newly synthesized or mature transcripts. While many RPBs are known to recognize certain nucleotide sequences in RNA, information is insufficient for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In the present study, the cytoplasmic localization of LINC00857 in CRC cells indicated the post-transcriptional effect of LINC00857 on gene expression. Furthermore, RBPs exert crucial effects by post-transcriptionally regulating gene expression (28), including pre-mRNA splicing, mRNA stabilization, mRNA localization and translation (17,38). The present study hypothesized the potential regulatory pattern of LINC00857 in which LINC00857 interacted with RBPs to stabilize mRNA.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, the cytoplasmic localization of LINC00857 in CRC cells indicated the post-transcriptional effect of LINC00857 on gene expression. Furthermore, RBPs exert crucial effects by post-transcriptionally regulating gene expression (28), including pre-mRNA splicing, mRNA stabilization, mRNA localization and translation (17,38). The present study hypothesized the potential regulatory pattern of LINC00857 in which LINC00857 interacted with RBPs to stabilize mRNA.…”
Section: Discussionmentioning
confidence: 69%
“…To better understand the mechanistic basis of the RNA-binding-protein-mediated regulation of biological functions, including brain functions, it is important to identify target mRNAs for RNA-binding proteins. Various methods have been developed for this purpose [234,235].…”
Section: Methods For Identifying Rna-protein Interactionsmentioning
confidence: 99%
“…As the characterization of physiological protein-RNA interactions is essential to understand how mRNA is transcribed and processed in cells, various methods have been developed to detect such transient and faint interactions, which has been reviewed in several articles [13][14][15]. These methods can be classified into protein-centric and RNA-centric methods.…”
Section: Figurementioning
confidence: 99%